2019
DOI: 10.3390/ijms20143447
|View full text |Cite
|
Sign up to set email alerts
|

Hair Growth Promoting Effect of 4HGF Encapsulated with PGA Nanoparticles (PGA-4HGF) by β-Catenin Activation and Its Related Cell Cycle Molecules

Abstract: Poly-γ-glutamic acid (γ-PGA)-based nanoparticles draw remarkable attention as drug delivery agents due to their controlled release characteristics, low toxicity, and biocompatibility. 4HGF is an herbal mixture of Phellinus linteus grown on germinated brown rice, Cordyceps militaris grown on germinated soybeans, Polygonum multiflorum, Ficus carica, and Cocos nucifera oil. Here, we encapsulated 4HGF within PGA-based hydrogel nanoparticles, prepared by simple ionic gelation with chitosan, to facilitate its penetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 83 publications
0
12
0
Order By: Relevance
“…DPCs are multipotent hair follicle stem cells, which are stimulated to differentiate and proliferate during regrowth of hair follicles 4042. It has also been reported that the morphology of stem cell-like DPCs is flattened and polygonal,43 which is closely associated with the enlargement of hair bulb 26,42,44,45. Thus, we investigated whether PGA-4HGF treatment induces morphological changes in primary DPCs.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…DPCs are multipotent hair follicle stem cells, which are stimulated to differentiate and proliferate during regrowth of hair follicles 4042. It has also been reported that the morphology of stem cell-like DPCs is flattened and polygonal,43 which is closely associated with the enlargement of hair bulb 26,42,44,45. Thus, we investigated whether PGA-4HGF treatment induces morphological changes in primary DPCs.…”
Section: Resultsmentioning
confidence: 97%
“…As this new hydrogel formulation has the potential to deliver hair growth-promoting compounds more efficiently into hair follicles, it can be potentially utilized in the field of hair-care cosmeceuticals. Further studies demonstrating the mechanisms underlying promotion of hair growth,26 as well as human testing are underway in our group, with an aim to launch new PGA-4HGF-based hair growth-promoting products in the market.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Western blotting was performed as previously described [ 63 ]. Briefly, A549 cells (1 × 10 6 ) were incubated for 6 h in 6 well plates, pre-treated with GR and GR-SC65 (100 μg/mL) for 1 h, followed by treatment with PM (100 μg/mL).…”
Section: Methodsmentioning
confidence: 99%